ANALISIS PENGGUNAAN YOUTUBE SEBAGAI MEDIA PEMBELAJARAN DALAM PEMAHAMAN KONSEP DASAR MATEMATIKA SISWA KELAS II SD - Shelya Hanum Prasasti; Sri Mulyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the use of YouTube as a learning medium in enhancing students’ understanding of basic mathematical concepts in second-grade students at SDIT Mutiara Insan Sukoharjo. The problem addressed in this study is the difficulty of students in understanding abstract mathematical concepts when using conventional learning methods. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving teachers, students, and the school principal as research subjects. Data validity was ensured through triangulation techniques, while data analysis was conducted using data reduction, data display, and conclusion drawing. The results indicate that the use of YouTube as a learning medium was implemented systematically through planning, implementation, and evaluation stages. The integration of audiovisual content from YouTube helped increase students’ attention, motivation, and engagement in learning. Furthermore, students demonstrated improved understanding of basic mathematical concepts, as shown by their ability to explain concepts, provide examples, and solve problems. However, some challenges were found, such as unstable internet connections and the need for appropriate content selection. Overall, YouTube is considered an effective learning medium to support the understanding of mathematical concepts in elementary school students when used appropriately.